The Changing Faces of Aawambo Musical Arts. Minette Mans. 2017. Switzerland: Basel Afrika Bibliographien. 56 bw figures (photographs, sketches), 24 transcriptions, glossary, bibliography, index, 188pp. - McConnachie, Boudina (International Library of African Music, 2017)
pages: 175-177
Keywords: African Music